La chimie dans la vie quotidienne - Agouridas, Constantin; Bernier, Jean-Claude; Olivier, Danièle; Rigny, Paul (Collection Chimie et ... junior., 2018)
With Max and Léa, discover and understand the contribution of chemistry in the design of everyday objects, to your well-being, to your quality of life, and to respect for the environment. Max and Léa will also show you that, behind this chemistry of everyday life, there is a strong industry, dynamic research, jobs and diverse and varied trades.